Potential candidate probiotic Bacillus amyloliquefaciens strain NO10 SA8 in cholesterol assimilation and amino acid production - Sukmawati; Hardianti , Fatimah; Amalia, Falina; Kaway, Sancy (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2025)
Probiotics are known as beneficial microorganisms that, when administered in appropriate amounts, can provide health benefits to their host. The ability of probiotics to produce amino acids is crucial to consider, as amino acids are essential components for the growth and development of organisms. The objective of this study is to analyze the ability of Bacillus amyloliquefaciens strain NO10 SA8 to assimilate cholesterol and its capability to produce amino acids. This study employed a descriptive method, including cholesterol assimilation and analysis of amino acid types produced by the potential probiotic bacterium Bacillus amyloliquefaciens strain NO10 SA8. The results of this study showed that Bacillus amyloliquefaciens strain NO10 SA8 ability demonstrated a relatively high cholesterol assimilation capacity—approximately 69.75% compared to the positive control. This indicates that the strain has potential to be used as a cholesterol-lowering agent in functional applications, such as probiotics or dietary supplements.it was capable of assimilating cholesterol. Furthermore, it was able to produce various amino acids, except for L-Histidine,  L-Tyrosine, and L-Tryptophan. The conclusion of this study is that Bacillus amyloliquefaciens strain NO10 SA8 has potential as a probiotic strain because it demonstrated the ability to assimilate cholesterol 69.75% compared to the positive control,  and producing amino acids.